¿Existe una brecha cambiaria en el Perú? - Moguillansky, Graciela (1996)
As in other Latin American economies, in recent years, Peru has been experiencing a strong influx of foreign capital which, on the one hand has speeded up economic growth but, on the other, necessitated cautious monetary and exchange policy to prevent economic instability in this context, it has been difficult to keep the real exchange rate high and exporters and certain branches of Peruvian industry have been hurt by its fall. The question the article tries to answer is whether the exchange rate really is lopsided or whether exchange rate shifts occur in response to long-term factors, be they internal or external, that have suppressed the rate to lower levels than those of the 1980s. To do this the author used the methodology of Johansen and Juselius to calculate a co-integration vector, which revealed a lack of parity between the quoted value and that of a balanced rate. The author’s calculations show that the local currency has been considerably overvalues for the past four years. The reason for this behavior can be ascribes to the heavy influx of short-term investment, the sheer volume of which has made it difficult to keep the real exchange rate up.